The OECD enlargement in Latin America and the Brazilian candidacy - Mello,Flavia de Campos (2020)
Abstract This article examines the OECD’s enlargement process as an important dimension for understanding global economic governance. It focuses on the Brazilian candidacy, stemming first from the OECD’s strategies towards the BRICS countries, but also towards Latin America, where the organization’s enlargement has expanded its members in a matching process with the incorporation of European countries. The OECD became a high priority for Brazil in the context of a significant change of orientations on economic reforms and foreign policy choices. By looking at the experience of Latin American countries regarding their accession processes to the OECD, the article concludes referring to the organization as an expanding Western-led institution aimed at promoting a liberal economic agenda through enhanced global governance mechanisms.